Socialization the Importance of Completing the Completeness of Mental Care CPPT in Hb Saanin Hospital - Nurhasanah Nasution; Sayati Mandia (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
One effort to improve the quality of medical record documentation is through quantitative analysis. Quantitative analysis of medical record documents includes identification, recording, reporting, and authentication review. Medical record documentation supports achieving one of the Minimum Service Standards (SPM) for medical records, namely the completeness of filling in medical records 100%. One of the important completeness of medical record files is CPPT, Integrated records support medical team coordination. All members of Professional Care Providers (PPA), such as doctors, nurses, and related experts, can access the same information. This facilitates better communication and collaboration in decision-making regarding patient care. The incomplete filling out of the CPPT has made the staff interested in conducting outreach regarding the completeness of the CPPT at RJ. HB Saanin. The activity is planned to be carried out over two days at RSJ HB Saanin in March 2023. The activity method is socializing the proper procedures for completing the CPPT to Professional Care Providers (PPA). The implementation of community service is related to the importance of filling out CPPT at RSJ. Prof. HB. Saanin went well and smoothly. The material provided includes Basic concepts of CPPT, the Purpose of filling out the CPPT, Benefits of filling out CPPT, and Steps to fill out the CPPT. In general, PKM activities ran smoothly and well, the activity was attended by 16 participants consisting of the PKM Team, hospital leaders, and staff consisting of doctors, nurses, and medical records officers. The activities were carried out on time, the training participants were enthusiastic about the activities as evidenced by the increasing scores on the post-test.